Pengaruh Kompensasi, Motivasi Kerja Dan Lingkungan Kerja Terhadap Loyalitas Kerja Karyawan Dinas Lingkungan Hidup Kota Malang - Adinda Bella Priwahyu Fani; Hadi Sunaryo; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted at the Department of the Environment of Malang City. The purpose of this study was to examine and describe the effect of compensation, work motivation and work environment on employee loyalty at the Malang City Environment Service.The variables used are compensation, work motivation and work environment as independent variables, while work loyalty is the dependent variable. The sample used in this study were 65 civil servants (PNS) of the Malang City Environment Service using the random proportional stratification method. Methods of data collection by collecting primary and secondary data. The analysis used includes instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing and coefficient of determination test using multiple regression analysis with the help of SPSS 25 for windows software.The results showed that simultaneously compensation, work motivation and work environment had an effect on work loyalty, while partially compensation and work motivation had a significant effect on the work loyalty of employees of the Environmental Service of Malang City and the variable of the work environment had no significant effect on the work loyalty of employees of the Environmental Service. Malang city. Keywords: Compensation, Work Motivation, Work Environment, and Work Loyalty